Non-Formal Education Financing Management (Analysis of The Concept and Its Implications for Improving the Quality of Education) - Lau, Elfreda Aplonia; Jonathan, Robin; Militina, Theresia; Gupta, Sachin (Journal of Nonformal Education, 2024)
This study aims to analyze the basic concept of education financing and its implications for improving the quality of education. This study uses the library research method. The results of the study show that improving the quality of an educational institution / institution is the hope and desire of the community who uses educational services. Therefore, to realize this, various strategic efforts have been made by the government and the community as education managers and stakeholders. Among them, what the government has done is to design national education standards. Based on the National Education System Law Number 20 of 2003, there are 8 national standards that aim to improve the quality of an educational institution. Based on government regulations, one of the eight national education standards is the financing standard. Education financing is the most important and inseparable thing in education management activities. So, among other things, the government’s policy is to roll out BOS funds at the school level. Education financing and funding managed by schools/madrasas must be transparent in order to create accountability. If it can be accounted for, the credibility of the educational institution will increase. If it is credible, it will automatically improve the quality of educational institutions. To achieve this, the government regulates the standards for term financing.